PEMANFAATAN LIMBAH CANGKANG KEONG SAWAH (Bellamya javanica) UNTUK SINTESIS HIDROKSIAPATIT DENGAN MODIFIKASI PORI MENGGUNAKAN PATI UBI JALAR - Indriani, Yunida; Iswadi, Iswadi; Fuadi, Nurul (Universitas Islam Negeri Alauddin Makassar, 2018)
The research has been carried out by utilizing pore conch shell waste using sweet potato starch to make porous Hydroxyapatite using porogen sweet potato starch by precipitation method and to determine the bioactive properties of apatite hydroxy and the growth of apatite crystals using Simulated Body Fluid (SBF). This study used wet precipitation method. The results of the analysisÂ using XRD show that the HAp phase has been formed. The morphology of HAp based on SEM results shows that HAp pores modification is produced in the composition of HAp added with 20% sweet potato starch with 6 hour sonication wich results in pore size from the range 0,23-3,37 Âµm. This result is not correlate with the theory that the best pore modification is produced in the composition of HAp added with 30% starch. This is because there are difference characters of each sweet potato used. The result of in vitro tests on synthesis HAp samples and 7 days porous HAp have shown the growth of apatite crystals in SBF solution media (Simulated Body Fluid).